COMPARING THE EFFECTS OF TRADITIONAL AND SIMULATION-BASED NURSING EDUCATION ON CLINICAL COMPETENCE AND CRITICAL THINKING SKILLS: A QUASI-EXPERIMENTAL STUDY - Hanan Obaid Alanazi, Ahlam Fhad Alanazi, Dhuha Nasser Alanazi, Reem Khalaf Alanazi, Futayem Doweh Alanazi, Mashael Badah Alsahl (Chelonian Research Foundation, 2022)
Nursing education plays a crucial role in preparing competent and critically thinking nurses. This quasi-experimental study aimed to compare the effects of traditional and simulation-based nursing education on clinical competence and critical thinking skills among nursing students in Hafar Al-Batin, Saudi Arabia. A sample of 120 nursing students was divided into two groups: the traditional education group (n=60) and the simulation-based education group (n=60). The study utilized the Creighton Competency Evaluation Instrument (CCEI) to assess clinical competence and the California Critical Thinking Skills Test (CCTST) to evaluate critical thinking skills. Data were analyzed using descriptive statistics, independent t-tests, and ANCOVA. The findings revealed that the simulation-based education group had significantly higher scores in clinical competence (p<0.001) and critical thinking skills (p<0.01) compared to the traditional education group. The study highlights the effectiveness of simulation-based education in enhancing clinical competence and critical thinking skills among nursing students. The results suggest that incorporating simulation-based learning into nursing curricula can better prepare students for real-world clinical practice and improve patient outcomes.